2005
DOI: 10.1590/s0100-879x2005001200015
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of selective serotonin reuptake inhibitors on neuroleptic-induced catalepsy in mice

Abstract: Depression found in Parkinson disease (PD) usually responds to selective serotonin reuptake inhibitors (SSRIs). Drugs that modify experimental neuroleptic catalepsy (NC) might affect extrapyramidal symptoms in PD. Therefore, the effects of SSRIs on NC were tested in mice, 26-36 g, separated by sex. Catalepsy was induced with haloperidol (H; 1 mg/kg, ip) and measured at 30-min intervals using a bar test. An SSRI (sertraline, ST; paroxetine, PX; fluoxetine) or vehicle (C) was injected ip 30 min before H. Dunnett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…For example, selective 5-HT-reuptake inhibitors (SSRIs) attenuate haloperidolinduced catalepsy in mice (6). In addition, the 5-HT 1A -receptor agonists 8-hydroxy-2-(di-n-propylamino) tetralin (8-OH-DPAT) and buspirone and the 5-HT 2A/ 2C -receptor agonist 2,5-dimethoxy-4-iodoamphetamine (DOI) attenuate D 2 -receptor-mediated catalepsy (7 -11).…”
mentioning
confidence: 99%
“…For example, selective 5-HT-reuptake inhibitors (SSRIs) attenuate haloperidolinduced catalepsy in mice (6). In addition, the 5-HT 1A -receptor agonists 8-hydroxy-2-(di-n-propylamino) tetralin (8-OH-DPAT) and buspirone and the 5-HT 2A/ 2C -receptor agonist 2,5-dimethoxy-4-iodoamphetamine (DOI) attenuate D 2 -receptor-mediated catalepsy (7 -11).…”
mentioning
confidence: 99%
“…Group III served as standard group that received 5mg/kg flouxetine, i.p (Pires at al., 2005) and haloperidol (1mg/kg, i.p). Group IV served as drug treated group that received MEFV (500mg/kg, p.o) and haloperidol (1mg/kg, i.p).…”
Section: Haloperidol Induce Catalepsy (Hic) In Micementioning
confidence: 99%
“…Ja¨rbe et al (2002) have shown that systemic administration of rimonabant (a synthetic cannabinoid CB 1 receptor) has reversed the effect of systemic administration of D 9 -THC completely (Ja¨rbe et al, 2002). As we know reserpine blocks the ability of aminergic transmitter vesicles to be reuptaked and restore dopamine, norepinephrine and serotonine, incomplete reverse of ACPA effects can be related to interfering of other neurotransmitters such as dopamine or serotonine (Pires et al, 2005). Piers et al in 2005 has demonstrated a role for serotonine and it's receptors in cannabinoids induced catalepsy.…”
Section: Figurementioning
confidence: 99%